PERSEPSI GURU TENTANG BUDAYA SEKOLAH PADA SMA NEGERI DI KABUPATEN LIMA PULUH KOTA - Ika Purnama Sari (Jurnal Bahana Manajemen Pendidikan, 2014)
The study aims to know how the implementation of school culture on Senior High School in District of Lima Puluh Kota.The research is a descriptive quantity study with a population of 484 people, using stratified disproportionate random sampling technique which is totaled 83 people.The data were analize by using score of average (Mean). The results of the study show that trust, cooperation, and responsibility inherent to the goal of the school culture (overall score 3.15 of 4.00). However, school still has to strengthen the culture through better trust, cooperation, and responsibility. Key word: Trust, Cooperation, and Responsibility